(untitled) - Hartley, Karen; 1949-; 1940-; Taylor, Philip; Macro, Chris; 1949- (Chicago, 2003)
A simple introduction to the physical characteristics, diet, life cycle, predators, habitat, and lifespan of caterpillars.
Includes bibliographical references (p. ).
Accelerated Reader AR
Keywords: Caterpillars; Juvenile literature